BUILDING A COMPREHENSIVE KNOWLEDGE BASE ON SUNFLOWER RESEARCH OVER MORE THAN 24 YEARS OF PUBLISHING THE ISJ HELIA - Sakač, Z.; Škorić, D. (Helia (Novi Sad), 2014)
Journal Helia started his "mission" nearly 36 years ago, very unpretentious, as an information bulletin FAO Research Network on Sunflower, with the founders intention to allow quick and easy exchange of knowledge gained from experimental field trials of improving and breeding so important oilseed crop species, such as sunflower. Over time, the number of scientists gathered around the project development and promotion of sunflowers growing under the FAO Research Network on Sunflower has risen slowly but surely, the projects became more extensive, complex and serious. The abundance of scientific research results, realized in the framework of a research network, imposed the direction of evolution journal Helia in scientific journal with internationally recognized quality, peer-reviewed papers and relatively highly ranked in the scientific society. Since the beginning in Serbia, the Journal was published by the Institute of Field and Vegetable Crops, as the publisher and editorial office headquarters, under the auspices of F.A.O. and ISA until 2006th. In 2007 the editorial office was moved to the Serbian Academy of Sciences and Arts, branch in Novi Sad, which also assumed the role of the main publisher, while the Institute remained to be a co-publisher. Since 1990 a total of 24 volumes with 47 regular and two extraordinary numbers have been published by the scientific journal HELIA. That’s a pretty impressive library with 6900 pages of printed material in 746 scientific papers in English. So far 2125 authors and co-authors of scientific papers from 43 countries from all continents have participated in publishing scientific papers in the journal and many authors have published a number of papers. All submitted manuscripts are subject to anonymous, international review (so-called "single-blind peer review", where the authors of the papers do not know who the reviewers, but the reviewers know who the authors of the papers) and published in the journal only after receiving a positive review by two independent reviewers and the final opinion of the editor. Considering the impact factor of the ISJ Helia in the last 10 years, according to citation indicators of some papers published in the journal Helia, it can be observed relatively high levels over the past 10 years, with a trend of significant increase in 2011th and 2012th. Focusing on that parameter, and the relatively high two-and five-year impact factors in 2011th and 2012th, we can be very pleased with these trends, which lead to our journal ranked near to relatively influential journals globally.